POTENSI FLAVONOID TERHADAP PERBAIKAN HISTOPATOLOGI AORTA MENCIT APOE-/- DENGAN DIET TINGGI LEMAK SYSTEMATIC LITERATURE REVIEW - Hilmi Adyatma, Hilmi (2021)
Non-communicable diseases account for more than 36 million deaths each year (63% of all deaths). Globally, non-communicable disease (PTM) which causes the most deaths every year is cardiovascular disease. One of the cardiovascular diseases is coronary heart disease. The cause of coronary heart disease is acute coronary syndrome. More than 90% of acute coronary syndrome (ACS) is a result of atherosclerotic disorders. Therefore, research on the potential for flavonoids to improve the histopathology of atherosclerosis is necessary to provide information about alternative drugs that can be used by patients. The aim of this research using systematic literature review research methodology is expected to identify the potential of flavonoids to improve the aortic histopathology of ApoE-/-mice on a high-fat diet. Methods: Systematic literature review by conducting literature searches using PubMed and Google Scholar. Literature that discusses flavonoids, ApoE-/- mice, high fat diet, aorta, and atherosclerosis. Results: There were 8 studies which concluded that flavonoids could inhibit or reduce the enlargement or further formation of aortic atherosclerotic plaque in ApoE-/- mice on a high-fat diet. Conclusion: Flavonoids have the potential to inhibit or reduce the enlargement or further formation of aortic atherosclerotic plaque in ApoE-/- mice on a high-fat diet.